2020
DOI: 10.1002/rth2.12403
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis is driven by protease‐activated receptor‐1 expressed by hepatic stellate cells in experimental chronic liver injury

Abstract: Background Blood coagulation protease activity is proposed to drive hepatic fibrosis through activation of protease‐activated receptors (PARs). Whole‐body PAR‐1 deficiency reduces experimental hepatic fibrosis, and in vitro studies suggest a potential contribution by PAR‐1 expressed by hepatic stellate cells. However, owing to a lack of specific tools, the cell‐specific role of PAR‐1 in experimental hepatic fibrosis has never been formally investigated. Using a novel mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…This particularity defines CAFs as sensors of extravascular coagulation, especially in the context of chronic inflammation, prone to fibrosis and malignant transformation [94]. Liver fibrosis, an established precancerous state, highlights the role of PAR1 in collagen I deposition [95,96]. Thrombin can also stimulate the release of active TGF-β [97].…”
Section: Tamsmentioning
confidence: 99%
“…This particularity defines CAFs as sensors of extravascular coagulation, especially in the context of chronic inflammation, prone to fibrosis and malignant transformation [94]. Liver fibrosis, an established precancerous state, highlights the role of PAR1 in collagen I deposition [95,96]. Thrombin can also stimulate the release of active TGF-β [97].…”
Section: Tamsmentioning
confidence: 99%
“…In chronic liver disease, HSCs express upregulated PAR1 ( Fiorucci et al, 2004 ). Furthermore, it was found that removal of stellate cell-specific PAR1 produced a 35% reduction in the accumulation of liver collagen ( Poole et al, 2020 ) and PAR1 deficient mice appeared to be protected from CCl4-induced liver fibrosis ( Rullier et al, 2008 ; Kallis et al, 2014 ). In the line with these findings, the current study showed that PAR1 expression was significantly increased in the DEN+CCl4 intoxicated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation also plays a role in chronic liver injury; the fenestrated sinusoidal endothelial cells allow plasma flow from sinusoidal blood into the space of Disse [8], thereby granting contact of clotting factors with hepatocytes and cholangiocytes and facilitating local hemostatic action. Several studies demonstrate the role of hepatic coagulation activation in the pathology of liver fibrosis [13][14][15]. The key enzyme of coagulation is thrombin, which is generated by hepatocytes in a cholestatic setting in vivo and converts fibrinogen leading to fibrin deposits within the liver parenchyma [16].…”
Section: Introductionmentioning
confidence: 99%
“…The key enzyme of coagulation is thrombin, which is generated by hepatocytes in a cholestatic setting in vivo and converts fibrinogen leading to fibrin deposits within the liver parenchyma [16]. However, the predominant mechanism of thrombin-induced liver injury is caused by protease-activated receptors (PARs) on neutrophils and hepatic stellate cells which mediate neutrophil activation and induction of profibrotic mediators [15,17].…”
Section: Introductionmentioning
confidence: 99%